ANALISIS TINGKAT KEPUASAN TAMU TERHADAP PELAYANAN HOUSEKEEPING BERDASARKAN ONLINE CUSTOMER REVIEWS DI GRANDMAS PLUS HOTEL SEMINYAK - Sutrisnawati, Ni Ketut; Meciliana Merlin; Ida Bagus Nyoman Bala Putra; Ni Gusti Ayu Nyoman Budiasih (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
This study was conducted to analyse guest satisfaction levels with housekeeping services based on online customer reviews at Grandmas Plus Hotel Seminyak. Fierce competition in the tourism sector poses a challenge for industry players to continue providing quality services in order to create customer satisfaction. Customer satisfaction is a barometer of a company's success, in this case the hospitality industry, in meeting consumer needs and desires. Customer satisfaction can build and maintain the long-term stability of a business and provide profits and success for the business. The more consumers who are satisfied, the more opportunities there are for the hotel's success. Meanwhile, dissatisfied consumers can damage the reputation or image, which can have an impact on the hotel's business continuity. The research method used is descriptive qualitative, focusing on customer reviews related to the duties and responsibilities of the housekeeping department. Guest review data was collected from January 2025 to June 2025 through documentation methods sourced from several widely used online travel agent platforms and easy access to consumer reviews. The results of the study show that several online travel agent platforms gave excellent ratings, but there were complaints related to cleanliness as one of the tasks of the housekeeping department. These comments need to be analysed to identify the factors that cause guest satisfaction and dissatisfaction, especially in the housekeeping department. With this analysis, it is hoped that there will be an improvement in service so that guest satisfaction is maintained and solutions can be found to the problems that arise. Thus, it is hoped that the Grandmas Plus Seminyak Hotel will remain superior and able to compete amid increasingly fierce competition.